The Modal Particles in the Storybook åŽŸæˆ‘è¿™ä¹ˆæ£’ YuÃ¡nlÃ¡i WÏ ZhÃ¨me BÃ ng By Li Huizhen Partikel Modalitas dalam Buku Cerita åŽŸæ¥æˆ‘è¿™ä¹ˆæ£’ YuÃ¡nlÃ¡i WÇ’ ZhÃ¨me BÃ ng Karya Li Huizhen - Handayani, Yayan Yunita; Chandra, Yulie Neila (Bambuti, 2020)
Particles in Mandarin can be divided into three kinds, namely structural, aspectual, and modality or modal particles. The particles have their own functions, as well as having grammatical meanings. This article discusses the particles of modality in the children's storybook entitledåŽŸæˆ‘è¿™ä¹ˆæ£’(YuÃ¡nlÃ¡i WÏ ZhÃ¨me BÃ ng) 'I'm So Great' by Li Huizhen. Particles of modality are widely used in the context of the conversation in the storybook, namely å•Š a, å§ ba, å•¦la, äº†le, å•°luo, å—ma, å˜›ma, å“ªna, å‘¢ne, å‘€ya, å“Ÿyo. Through distributional analysis methods, as well as with the technique of evaporation and transfer analysis, the modality particles can be matched with phatic particles in Indonesian, such as 'ya', 'lah', 'sih', 'lho', and 'dong' which are generally located behind sentences, and some behind clauses. However, the meaning of the particles is uncertain and unsteady because each depends on the context of the sentence or the meaning of the sentence. The presence of modality particles in a sentence can change the meaning of a sentence, its type of sentence, or its language function.